Real-World Data on the Effectiveness and Safety of wilate for the Treatment of von Willebrand Disease - Sholzberg, Michelle; Khair, Kate; Yaish, Hassan; Rodgers, George; Cruz, Maria Sol; Mejía, Cesar Montaño; Čermáková, Zuzana; Matino, Davide; Teitel, Jerome; Barrie, Alpha; Werner, Sylvia; Prondzinski, Mario von Depka (TH Open, 2021)
Background The efficacy and safety of wilate (human von Willebrand factor/coagulation factor VIII) in patients with von Willebrand disease (VWD) has been demonstrated in clinical trials. Here, we present real-world data on the use of wilate for the routine care of patients with VWD.Objectives The objectives of this observational, prospective, phase 4 study were to evaluate the safety, tolerability, and effectiveness of wilate in on-demand treatment of bleeding episodes (BEs), long-term prophylaxis, and surgical prophylaxis among patients with any type of VWD.Methods Patients were enrolled at 31 study centers in 11 countries and followed for up to 2 years. Safety endpoints included adverse drug reactions (ADRs) and drug tolerability. Effectiveness was assessed using annualized bleeding rates (ABRs) during prophylaxis and predefined criteria for the treatment of BEs and surgical prophylaxis.Results A total of 111 patients (76 [68%] female) including 41 (37%) children were treated with wilate. Twenty-five patients received prophylaxis, 29 on-demand treatment, and 62 surgical prophylaxis. Tolerability was rated by patients as “excellent” for 96.2% of 6,497 infusions. No unexpected ADRs or thrombotic events were reported. Median ABR during prophylaxis was 1.9. Effectiveness was assessed as “excellent” or “good” by patients and investigators for 100% of BEs treated on-demand, 98% (patient rating) and 99% (investigator rating) of breakthrough BEs, and 99% of surgical procedures (investigator rating).Conclusion wilate was safe, well tolerated, and effective for the prevention and treatment of bleeding in pediatric and adult VWD patients in a real-world setting.
Keywords: factor VIII; observational study; prophylaxis; von Willebrand disease; von Willebrand factor